2023
DOI: 10.3390/nu15224825
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate Counting, Empowerment and Glycemic Outcomes in Adolescents and Young Adults with Long Duration of Type 1 Diabetes

Elisabeth Jelleryd,
Anna Lena Brorsson,
Carmel E. Smart
et al.

Abstract: The complex treatment for diabetes type 1 (T1D) includes insulin dosing for every meal, which requires education and experience to achieve optimal outcomes. Advanced carbohydrate counting (ACC) is the recommended method. We studied ACC as part of a standard treatment with the aim to explore its associations with glycemic control and empowerment in adolescents and young adults. We used national registry data on glycemic outcomes, a study-specific questionnaire regarding the use of ACC and the Gothenburg Young P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…It has been suggested that if ACC skills are acquired at or near the onset of diabetes, the likelihood of continued utilization of the method by the child or adolescent is maximized [ 32 ]. This could be a rationale for tailoring the program specific to the newly diagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that if ACC skills are acquired at or near the onset of diabetes, the likelihood of continued utilization of the method by the child or adolescent is maximized [ 32 ]. This could be a rationale for tailoring the program specific to the newly diagnosed.…”
Section: Discussionmentioning
confidence: 99%